Reducing Immunogenicity of Pegloticase With Concomitant Use of Mycophenolate Mofetil in Patients With Refractory Gout: A Phase II, Randomized, Double‐Blind, Placebo‐Controlled Trial. Issue 8 (19th May 2021) - Khanna, Puja P.; Khanna, Dinesh; Cutter, Gary; Foster, Jeff; Melnick, Joshua; Jaafar, Sara; Biggers, Stephanie; Rahman, A. K. M. Fazlur; Kuo, Hui‐Chien; Feese, Michelle; Kivitz, Alan; King, Charles; et al.
Abstract : Objective: Pegloticase is used for the treatment of severe gout, but its use is limited by immunogenicity. This study was undertaken to evaluate whether mycophenolate mofetil (MMF) prolongs the efficacy of pegloticase. Methods: Participants were randomized 3:1 to receive 1, 000 mg MMF twice daily or placebo for 14 weeks, starting 2 weeks before receiving pegloticase and continuing while receiving intravenous pegloticase 8 mg biweekly for 12 weeks. Participants then received pegloticase alone from week 12 to week 24. The primary end points were the proportion of patients who sustained a serum urate level of ≤6 mg/dl at 12 weeks and the rate of adverse events (AEs). Secondary end points included 24‐week durability of serum urate level ≤6 mg/dl. Fisher's exact test and Wilcoxon's 2‐sample test were used for analyses, along with Kaplan‐Meier estimates and log rank tests. Results: A total of 32 participants received ≥1 dose of pegloticase. Participants were predominantly men (88%), with a mean age of 55.2 years, mean gout duration of 13.4 years, and mean baseline serum urate level of 9.2 mg/dl. At 12 weeks, a serum urate level of ≤6 mg/dl was achieved in 19 (86%) of 22 participants in the MMF arm compared to 4 (40%) of 10 in the placebo arm ( P = 0.01). At week 24, the serum urate level was ≤6 mg/dl in 68% of MMF‐treated patients versus 30% of placebo‐treated patients ( P = 0.06), and rates of AEs were similar between groups, with more infusion reactions occurring in the placebo arm (30% versus 0%). Conclusion: Our findings indicate that MMF therapy with pegloticase is well tolerated and shows a clinically meaningful improvement in targeted serum urate level of ≤6 mg/dl at 12 and 24 weeks. This study suggests an innovative approach to pegloticase therapy in gout.